2021
DOI: 10.3390/ijms222111420
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antiseizure Analysis of Diverse Natural Coumarin Derivatives in Zebrafish

Abstract: Coumarins are a well-known group of plant secondary metabolites with various pharmacological activities, including antiseizure activity. In the search for new antiseizure drugs (ASDs) to treat epilepsy, it is yet unclear which types of coumarins are particularly interesting as a systematic analysis has not been reported. The current study performed behavioral antiseizure activity screening of 18 different coumarin derivatives in the larval zebrafish pentylenetetrazole (PTZ) model using locomotor measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Due to their small molecular weight and high lipophilicity, coumarins can easily penetrate the blood-brain barrier; therefore, they are good candidates for drugs with (CNS) activity. So far, the antiseizure effects of various coumarins have been reported in a series of in vivo assays with rodents or zebrafish [9,[27][28][29][30]. Previously two other furanocoumarin derivatives, lucidafuranocoumarin A and bergamottin, were tested in the zebrafish PTZ-induced seizure model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their small molecular weight and high lipophilicity, coumarins can easily penetrate the blood-brain barrier; therefore, they are good candidates for drugs with (CNS) activity. So far, the antiseizure effects of various coumarins have been reported in a series of in vivo assays with rodents or zebrafish [9,[27][28][29][30]. Previously two other furanocoumarin derivatives, lucidafuranocoumarin A and bergamottin, were tested in the zebrafish PTZ-induced seizure model.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of seizures induced by PTZ suggests that the antiepileptic mechanism of halfordin is related to GABA. The affinity to the GABA A receptor is structurally dependent, and compounds with substitution in both C5 and C8 positions exert more potent antiseizure activity than those with moieties only in C5 or C8 [27]. Halfordin is substituted in three positions-C3, C4, and C5; compared to the compounds substituted in both C5 and C8, the antiseizure activity lower of halfordin was lower, yet still significant.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, PTZ seizures and identified anti-seizure compounds from these screens in zebrafish larvae are consistent with results from rodent studies [ 160 , 161 ]. The PTZ-induced seizure model in zebrafish larvae has also been used to screen a variety of natural compounds for anti-seizure activity [ 162 , 163 , 164 , 165 ]. These screens aimed to discover novel anti-seizure therapies for treating refractory seizure disorders.…”
Section: Current Aquatic Vertebrate Seizure Modelsmentioning
confidence: 99%
“…In addition, it is worth noting that there are one or more chiral centers in the structure of most coumarins and flavonoids, especially furanocoumarins and dihydroflavones, as shown in Figure 1. For furanocoumarins, oxyimperatorin, oxypeucedanin hydrate, oxypeucedanin, notopterol, and byakangelicol enantiomers constituents widely exist in traditional Chinese medicine as key biological activities [13][14][15], and there is a stereogenic center in their chemical structure in the form of enantiomers. Among them, the contents of oxypeucedanin, byakangelicol, and notopterol enantiomers have been separated by chiral columns and proved to be obvious stereoselective in Citrus essential oils and Notopterygium from different sources [16,17], but the long peak time and insufficient separation indicated that new methods are still needed.…”
Section: Introductionmentioning
confidence: 99%